PS-R03-3: INTERMITTENTLY SCANNED CONTINUOUS GLUCOSE MONITORING IN A DIFFICULT PATIENT WITH GESTATIONAL DIABETES MELLITUS AND SUBCLINICAL CUSHING'S SYNDROME: A CASE REPORT. (January 2023) - Iwahara, Akihide; Sugiyama, Kazutoshi; Tsuchiya, Tami; Itoh, Arata; Nakajima, Yuya; Saisho, Yoshifumi; Kinouchi, Kenichiro; Kobayashi, Sakiko; Miyashita, Kazutoshi; Irie, Junichiro; Meguro, Shu; Ikenoue, Satoru; et al.
Abstract : A 41-year-old woman was admitted to the obstetrics department because of epigastric pain, nausea, and fatigue at 31 weeks of gestation. She was suspected of subclinical Cushing's syndrome based on high plasma cortisol and low ACTH levels along with an incidentally discovered tumor in the left adrenal gland 4 years prior to conception. 3 months before admission, 75 g oral glucose tolerance test yielded one point positive (81–169–174 mg/dL) and diagnosis of gestational diabetes mellitus was made. Diet and exercise therapy was started on an outpatient basis. While blood glucose control had been favorable, she discontinued visits to outpatient clinics due to difficulty in physical activity. At the time of admission, blood glucose level was running more than 200 mg/dl, and self-monitoring of blood glucose (SMBG) and insulin self-injection therapy were proposed for immediate blood glucose control accordingly. However, the patient had psychiatric symptoms that were presumably associated with delusional disorder and subclinical Cushing's syndrome. As such, she refused to implement both procedures on account of a strong fear against puncture, which caused blood glucose management difficult. Despite understanding the necessity of SMBG and potential risks to the fetus, the patient frequently expressed anxiety and could not perform SMBG. Given the difficult circumstance, intermittently scanned continuous glucose monitoring was installed to reduce invasive procedures. As a result, blood glucose levels were under good control with 0.43 U/kg of insulin per day until the delivery by cesarean section at 34 weeks of gestation. A healthy infant weighing 2442 g was delivered without complications. Here we highlight utility and efficacy of intermittently scanned continuous glucose monitoring in a difficult patient with gestational diabetes mellitus and subclinical Cushing's syndrome.